SOPHOMORES-STUDENTS’ BEHAVIOR STRATEGIES IN A CONFLICT AT HIGHER EDUCATIONAL INSTITUTIONS - Pukhno, Svetlana (PSYCHOLOGICAL JOURNAL, 2019)
Theoretical analysis of such concepts as “adaptation”, “behavior strategies in a conflict” and this psychological phenomena significance in the course of training sophomores-future teachers at a higher educational institution are presented in the article. As a result of the modern research theoretical analysis, it is presented that the students’ socio-psychological adaptation includes professional-specific adaptation (adaptation to the content, educational activities conditions and organization, the educational and research work skills formation); individual’s adaptation to the social environment, building interpersonal relations in academic groups; personal style behavior formation; public requirements adoption for future professional activities. In the adaptation course, new personal and professionally important qualities are formed that ensure the realization of the future professional personal potential. The first educational period is important for a person to undergo a complex adaptation period of entry into professional life, as well as the formation of behavioral patterns during interpersonal interaction, among the components are behavioral strategies in conflict. In order to determine the behavior strategies in the students’ conflict and this psychological phenomenon significance in the sophomore students’ adaptation process at higher educational institutions, during the 2018-2019 educational year, a study was conducted on the basis of Sumy Pedagogical University named after A.S. Makarenka, in which 30 future teachers of foreign languages, computer science, mathematics, physics, arts have been reviewed. The sophomore students majority (73.3%) have high rates on the scale of adaptability to educational activities were determined in the study. This testifies the students’ possession of educational and organizational, educational and intellectual, educational and informational, educational and informative, educational and communicative skills that ensure success in educational activities. High rates on the scale of adaptability to the academic group, the students majority characteristic (80%), indicate the presence of a academic group favorable psychological climate, the difficulties lack in the interaction process, the group norms adoption of a new social group. According to the research conducted on behavior strategies in a conflict, it has been determined that sophomore students majority are characterized by the behavior strategy “Compromise”. This indicates the presence of communication skills, tolerance, mutual respect, willingness to accept and analyze alternatives in controversial issues, participate in discussions, and make collegial decisions. This strategy dominance is associated with sophomore students’ desire to maintain the developed relations balance, the formed group psychological climate, to avoid negative emotional escalation and conflict tension. Low adaptability indicators to the academic group, the presence of irrational behavioral strategies in a conflict, are the result of the students’ communication skills lack and skills, which require activation of psychological education (lectures and seminars with diagnostic elements), the introduction of communication and conflict studies into the educational process of higher educational institutions.